A new misalignment calibration method of portable geomagnetic field vector measurement system. (November 2020) - Pang, Hongfeng; Pan, Mengchun; Qu, Wei; Qiu, Lei; Yang, Jun; Li, Yuntao; Wan, Chengbiao; Zhu, XueJun
Highlights: The angles between magnetometer/INS and host platform frame coordinate are obtained. Equipment attitude, earth's magnetic dip and the projection value are not need. No specific equipment is need, and no precise or non-magnetic tool is need. It also provides a new way to calibrate system with different information output. Abstract: Geomagnetic field is widely used for remote sensing, environment observation, geoscience and geology research. A portable geomagnetic field vector measurement system is designed, but misalignment greatly influences measurement accuracy. It is calibrated by establishing interim coordinate without measuring the projection of geomagnetic field and gravity. In addition, earth's magnetic dip, the accurate attitude of equipment and careful operation in collection process are not need. It is easy to implement the experiment, and misalignment angles between sensors are calculated. Magnetometer, inertial navigation system, host platform frame and perpendicular platform are used in experiment. After calibration, North, Vertical and East vector measurement error are reduced to 3.9%, 4.7% and 6.6% respectively. Inclination and declination error are reduced from 4.374° and 4.974° to 0.173° and 0.309° respectively. Thus, it is convenient and effective for misalignment calibration.